2023
DOI: 10.1155/2023/6243771
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum FGF23 and Chronic Kidney Disease‐Mineral and Bone Abnormality Markers With Cardiac Structure Changes in Maintenance Hemodialysis Patients

Abstract: Background. CKD-MBD is a mineral and bone metabolism syndrome caused by chronic kidney disease. FGF23 is an important factor regulating phosphorus and is the main influencer in the CKD-MBD process. In this study, we observed the correlation among serum FGF23 and calcium, phosphorus and parathyroid hormone, and the correlation between FGF23 levels and cardiac structural changes in MHD patients. Methods. We examined serum FGF23 concentrations in 107 cases of MHD patients using the ELISA method, recorded demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The first presentation of CKD-MBD is mostly characterized by biochemical abnormalities. In advanced stages of the illness, individuals may have bone and muscular pain, weakness, fractures, and even avascular necrosis [5] . CKD patients had a significantly elevated prevalence of bone fractures.…”
Section: ~ 2 ~mentioning
confidence: 99%
“…The first presentation of CKD-MBD is mostly characterized by biochemical abnormalities. In advanced stages of the illness, individuals may have bone and muscular pain, weakness, fractures, and even avascular necrosis [5] . CKD patients had a significantly elevated prevalence of bone fractures.…”
Section: ~ 2 ~mentioning
confidence: 99%
“…Other studies highlighted the role of FGF-23 in predicting the progression of CAC [ 72 , 73 ], also independently from hyperphosphatemia, LVH and cardiac hypertrophy [ 74 ]. It has recently been shown that dialysis patients with higher interleukin-6 (IL-6) values experience greater progression than those with lower values [ 75 ].…”
Section: Prediction Of Cad In Patients With Eskdmentioning
confidence: 99%